ODPOWIEDZIALNOŚĆ INWESTORA WOBEC PODWYKONAWCÓW (ART. 6471 § 5 K.C.) - Jędrejek, Grzegorz (Zeszyty Prawnicze, 2017)
The Liability of an Investor to a Subcontractor (Art. 6471 § 5 k.c.) Summary The article answers a question w hether an investor in case of a contract for construction works will be liable to a subcontractor also when he paid the latter all dues (including the rem uneration). These doubts are grounded in the form ulation of art. 6471 § 5 of the Polish Civil Code, according to which the party concluding a contract with thesubcontractor and the investor as well as the performer bear a joint andseveral liability for the payment of remuneration due to the subcontractor for the performed construction works. Taking into consideration a linguistic interpretation of the provision, as presented in the doctrine, it should be considered that the investor’s payment of the remuneration for the work performed by the subcontractor is permissible. Nevertheless, the author takes a different position based on the functional interpretation and interpretation referring to the whole system of the civil law.